HERITAGE SITES IN VISAKHAPATNAM CITY: TYPOLOGIES, ARCHITECTURAL STYLES AND STATUS - Giduthuri, Viswanadha Kumar (European Scientific Journal, ESJ, 2013)
Heritage on mother earth was recognized as one of the important fields of human endeavor. Many nations around the world have been pursuing the subject for the benefit of present and future generations. In the process, several first order cities around the world have geared up to meet the requirement. However, second order cities in many nations, especially in developing countries like India did not yet raise to the occasion. Therefore, a comprehensive study on heritage and its preservation was taken up in Visakhapatnam, India and the present communication dealing with heritage sites in Visakhapatnam Metropolitan Region forms a part of it. During this attempt, a total of 44 cultural heritage sites were identified from the city and their architectural styles, typologies and status analyzed.